Physiomorphic Transformation in Extreme Endurance Migrants: Revisiting the Case of Bar-Tailed Godwits Preparing for Trans-Pacific Flights - Piersma, Theunis; Gill, Robert E.; Ruthrauff, Daniel R. (Frontiers in Ecology and Evolution, 2021)
In a 1998 paper entitled ‘Guts don’t fly: small digestive organs in obese bar-tailed godwits’ it was shown that the digestive organs were tiny and the fat loads huge in individuals suspected of embarking on a nonstop flight from Alaska to New Zealand. It was suggested that prior to migratory departure, these godwits would shrink the digestive organs used during fuel deposition and boost the size and capacity of exercise organs to optimize flight performance. In this paper we document the verity of the proposed physiomorphic changes by comparing organ sizes and body composition of bar-tailed godwits Limosa lapponica baueri collected midway during their fueling period (mid-September; fueling) with the previously published data for godwits that had just departed on their trans-Pacific flight (19 October; flying). Mean total body masses for the two groups were nearly identical, but nearly half of the body mass of fueling godwits consisted of water, while fat constituted over half of total body mass of flying godwits. The two groups also differed in their fat-free mass components. The heart and flight muscles were heavier in fueling godwits, but these body components constituted a relatively greater fraction of the fat-free mass in flying godwits. In contrast, organs related to digestion and homeostasis were heavier in fueling godwits, and most of these organ groups were also relatively larger in fueling godwits compared to flying godwits. These results reflect a prioritization of organ and muscle groups related to energy acquisition in fueling godwits and to flight-related exertion in flying godwits. The extreme physiomorphic changes apparently occur over a short time window (≤1 month). We conclude that the inferences made on the basis of the 1998 paper were correct. The cues and stimuli which moderate these changes remain to be studied.